Pengaruh Financial Slack, Free Cash Flow, dan Firm Size Terhadap Corporate Social Responsibility Expenditure (CSRE) Pada Perusahaan LQ 45 - Putri Pawitan, Latifa; Saleh Sadikin, Dikdik; Budhijana, R. Bambang (Jurnal Keuangan dan Perbankan, 2024)
This study aims to determine the relationship between financial slack, free cash flow, and firm size on corporate social responsibility expenditure. This study uses data from companies listed on the LQ 45 index on the Indonesia Stock Exchange. The sampling technique in this study used a purposive sampling technique with predetermined criteria. The research method used in this research is a linear regression analysis technique using Eviews 10 software. The results of this study show that simultaneously financial slack, free cash flow and firm size have a significant effect on CSR expenditure. Partially, financial slack has no effect on CSR expenditure, free cash flow has a positive effect on CSR expenditure, and company size has a negative effect on CSR expenditure. Meanwhile, firm age as a control variable in this study has no effect on CSR expenditure.